The Consumption Effects of the 2007–2008 Financial Crisis: Evidence from Households in Denmark - Jensen, Thais Lærkholm; Johannesen, Niels (American Economic Review, 2017)
Did the financial crisis in 2007–2008 spread from distressed banks to households through a contraction of the credit supply? We study this question with a dataset that contains observations on all accounts in Danish banks as well as comprehensive information about individual account holders and banks. We document that banks exposed to the financial crisis reduced their lending relative to nonexposed banks, which in turn caused a significant decrease in the borrowing and spending of their customers. The effects were persistent: borrowing remained lower through the postcrisis years and spending foregone during the crisis was not recovered. (JEL D12, D14, E21, E32, G01, G21)